1991
DOI: 10.1002/crat.2170260622
|View full text |Cite
|
Sign up to set email alerts
|

A Direct Method for Orientation Determination Using TEM (II). Experimental Example

Abstract: A recently described direct method for orientation determination using a transmission electron microscope (TEM) is demonstrated on an experimental example.Eine kiirzlich publizierte direkte Methode zur Orientierungsbestimmung mit einem Transmissionselektronenmikroskop (TEM) wird an einem experimentellen Beispiel demonstriert.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…It relies on the 3D reconstruction of lattice periodicities from images taken at different tilts. As in diffraction-based techniques 8,9,10,11,12,13,14 for obtaining 3D crystallographic information, and imagebased techniques in stereomicroscopy 15,16,17,18,19,20,21,22 and electron tomography 23,24,25,26,27,28,29,30,31 , 3D information is being inferred from slices of 2D projections. As followup, a recent direct determination of lattice parameters in three dimensions from images of a nanocrystal at two tilts 32 suggested that such lattice-only analysis strategies could be elegantly visualized using fringevisibility maps that were quite sensitive to the effects of crystal thickness.…”
mentioning
confidence: 99%
“…It relies on the 3D reconstruction of lattice periodicities from images taken at different tilts. As in diffraction-based techniques 8,9,10,11,12,13,14 for obtaining 3D crystallographic information, and imagebased techniques in stereomicroscopy 15,16,17,18,19,20,21,22 and electron tomography 23,24,25,26,27,28,29,30,31 , 3D information is being inferred from slices of 2D projections. As followup, a recent direct determination of lattice parameters in three dimensions from images of a nanocrystal at two tilts 32 suggested that such lattice-only analysis strategies could be elegantly visualized using fringevisibility maps that were quite sensitive to the effects of crystal thickness.…”
mentioning
confidence: 99%